Bilateral hip stability variation in the functional ambulation and kinetic parameters after total hip arthroplasty during leveled walking - Abd-Eltawab, Amany E.; Elsherbini, Dalia Mahmoud Abdelmonem; El Nashar, Eman Mohamad; Alshehri, Shaker Hassan; Alhefzi, Ali; Eldesoqui, Mamdouh; El-Sherbiny, Mohamed (Frontiers in Bioengineering and Biotechnology, 2024)
Objectives: This study determines gender variation, comparing the significance level between males and females related to functional ambulation characteristics after hip arthroplasty.The study focuses on the broader female pelvis and how it affects the rehabilitation regimen following total hip arthroplasty.In this cross-sectional study, twenty cases of right hip arthroplasty were divided into ten male and ten female cases, ages 40 to 65 years. The functional ambulation parameters (cadence, speed, and cycle time) were acquired from the GaitRite device, as well as kinematic values for hip frontal plane displacement and kinetic parameters for ground response force in the medial-lateral direction.Results: An independent t-test showed a significant difference in the kinematic parameter variables for the anterior superior iliac spine (ASIS), more significant trochanter displacement, and hip abduction angle between the operated and non-operated limbs for each group separately.Regarding the functional ambulation parameters, there was only a significant difference in the walking cadence between the operated and non-operated limbs for male and female groups.Moreover, the output variables of Ground Reaction Force (GRF) measures revealed significant differences between their operated and non-operated limbs. The linear regression model used was consistent with the current results, demonstrating a weak negative correlation between the inclination angle of the operated hip and gait speed for both male and female groups.Based on the findings, we conclude that improving a rehabilitated physical therapy program for the abductors of both male and female patients with operated and nonoperated limbs is essential to normalising the ground reaction force value, avoiding focus on the operated hip, and reducing the amount of time that the operated hip's abductors must perform. This involves exposing the surgically repaired limb to the risk of post-operative displacement or dislocation, particularly in female patients.